2022
DOI: 10.36472/msd.v9i8.779
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Uvulectomy: A common and potentially life-threatening practice in a developing country

Abstract: Objective: uvula. It is usually performed by non-medical personnel using mostly unsterile instruments. Notwithstanding the increasing number of health facilities, it is surprising that this aged-long crude practice with significant complications is still rampant in the 21st century. Material and Methods: This is a case series of four males with the age range of 5-months to four years who had traditional uvulectomy following febrile illnesses but with no improvement of symptoms. Thereafter, all presented late t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In a dissemination meeting we held in Luwero town with the district leadership, traditional surgeons, VHTs, and local leaders from the two sub counties, the surgeons confirmed that they have not had any complications. Similar sentiments have been reported among traditional practitioners [ 21 ] and caregivers [ 32 ], although earlier studies indicated there are several complications from traditional uvulectomy [ 20 , 24 27 , 36 ] including mortality [ 24 ]. In a study in Nigeria, 58% of patients did not clear symptoms that led to uvulectomy [ 25 ].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In a dissemination meeting we held in Luwero town with the district leadership, traditional surgeons, VHTs, and local leaders from the two sub counties, the surgeons confirmed that they have not had any complications. Similar sentiments have been reported among traditional practitioners [ 21 ] and caregivers [ 32 ], although earlier studies indicated there are several complications from traditional uvulectomy [ 20 , 24 27 , 36 ] including mortality [ 24 ]. In a study in Nigeria, 58% of patients did not clear symptoms that led to uvulectomy [ 25 ].…”
Section: Discussionsupporting
confidence: 65%
“…Similar sentiments have been reported among traditional practitioners [21] and caregivers [32], although earlier studies indicated there are several complications from traditional uvulectomy [20,[24][25][26][27]36] including mortality [24]. In a study in Nigeria, 58% of patients did not clear symptoms that led to uvulectomy [25].…”
Section: Plos Global Public Healthsupporting
confidence: 55%
See 1 more Smart Citation